2006
DOI: 10.1038/sj.leu.2404099
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of normal CD40/interleukin-4 immunoglobulin heavy chain switch signal leads to genomic instability in SGH-MM5 and RPMI 8226 multiple myeloma cell lines

Abstract: The processes mediating genomic instability and clonal evolution are obscure in multiple myeloma (MM). Acquisition of new chromosomal translocations into the switch region of the immunoglobulin heavy chain (IgH) gene (chromosome 14q32) in MM, often heralds transformation to more aggressive disease. Since the combined effects of CD40 plus interleukin-4 (IL-4) mediate IgH isotype class switch recombination (CSR), and this process involves DNA double strand break repair (DSBR), we hypothesized that CD40 and/or IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, CD40 is also known to exert proliferative effects as well. For example, soluble CD40 ligand is sufficient to induce proliferation of MM cells whereas normal B cells require both CD40 ligand and IL-4 for full activation [25], suggesting that CD40 ligand act differently on different cells, and that MM cells exist at a stage of differentiation or activation that does not require a second signal such as IL-4. Finally, CD40 stimulation has been shown to induce apoptosis or proliferation in different cell types despite the activation of the NF-κB pathway in both instances [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CD40 is also known to exert proliferative effects as well. For example, soluble CD40 ligand is sufficient to induce proliferation of MM cells whereas normal B cells require both CD40 ligand and IL-4 for full activation [25], suggesting that CD40 ligand act differently on different cells, and that MM cells exist at a stage of differentiation or activation that does not require a second signal such as IL-4. Finally, CD40 stimulation has been shown to induce apoptosis or proliferation in different cell types despite the activation of the NF-κB pathway in both instances [46].…”
Section: Discussionmentioning
confidence: 99%
“…DOHH-2 and SUDHL-4 were obtained from the Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH (DSMZ, Germany). The SGH-MM5 and SHG-MM6 human MM cell lines were developed in our laboratory from a patient with MM using a modified Dexter-type long-term tissue culture system, as described previously [25].…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in the CD40 receptor in MM cell lines and patient specimens have been described previously by us and others (3,49). This consideration as well as the propensity of irreversible genomic instability through CD40 binding (50) are also potential explanations for CD40 agonism and antagonism converging to a common apoptotic outcome in myeloma cells. Clearly, further molecular studies that are based on our gene expression array findings may help resolve this conundrum.…”
Section: Discussionmentioning
confidence: 99%
“…RPMI 8226 MM, CESS Epstein-Barr virus (EBV)-transformed normal B cells, K562 chronic myeloid leukemia (CML), and HL-60 APL human cell lines were all purchased from the American Type Culture Collection (ATCC, Rockville, MD). The EBV-negative SGH-MM5 human MM cell line (CD10+ CD19- CD20- CD38+ CD40+ CD45+ CD56+ CD138+) was developed in our laboratory under the Singapore General Hospital (SGH) Institutional Review Board (IRB) good research practice guidelines, from a patient with MM using a modified Dexter-type long-term tissue culture system, which was previously described [ 23 ]. All cell lines were cultured in RPMI 1640 medium (Invitrogen, Gibco, Grand Island, NY) supplemented with 10% fetal calf serum (FCS) at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have suggested that the Ku86 variant seen in lymphocytes may be due to cleavage by proteases induced during biochemical isolation [ 20 - 22 ]. Considering the increased amount of genomic instability seen in MM, the disregulated CD40/interleukin-4 (IL-4) pathway in MM cells [ 23 ], and the role of Ku in DNA DSBR and non-homologous end-joining (NHEJ), we investigated the presence of Ku86 and its variants in MM cells, and compared them to T lymphocytes and other cell lines. We found that unlike human T lymphocytes, the detection of 69-kDa Ku86 (Ku86v-N) variant is not likely due to in vitro generated protease cleavage.…”
Section: Introductionmentioning
confidence: 99%